2011
DOI: 10.1128/aac.00879-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Activity of Wall Teichoic Acid Biosynthesis Inhibitors against Staphylococcus aureus Isolates

Abstract: Staphylococcus aureus is the leading cause of invasive and superficial human infections, is increasingly antibiotic resistant, and is therefore the target for the development of new antimicrobials. Compounds (1835F03 and targocil) were recently shown to function as bacteriostatic inhibitors of wall teichoic acid (WTA) biosynthesis in S. aureus. To assess the value of targeting WTA biosynthesis in human infection, it was therefore of interest to verify the involvement of WTA in bacterial binding to human cornea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…Because of its importance in vivo and in resistance to ␤-lactam antibiotics S. aureus WTA represents a very attractive target for the development of new antibiotics. Recently several promising novel compounds have been developed that inhibit TagO or the WTA transporter TagGH thereby rendering methicillin-resistant S. aureus (MRSA) susceptible to ␤-lactams Farha et al, 2013;Suzuki et al, 2011;Wang et al, 2013). Thus, WTA inhibitors could become useful for blocking S. aureus adhesion to host cells or for sensitizing MRSA to ␤-lactams.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its importance in vivo and in resistance to ␤-lactam antibiotics S. aureus WTA represents a very attractive target for the development of new antibiotics. Recently several promising novel compounds have been developed that inhibit TagO or the WTA transporter TagGH thereby rendering methicillin-resistant S. aureus (MRSA) susceptible to ␤-lactams Farha et al, 2013;Suzuki et al, 2011;Wang et al, 2013). Thus, WTA inhibitors could become useful for blocking S. aureus adhesion to host cells or for sensitizing MRSA to ␤-lactams.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these methicillin-resistant S. aureus (MRSA) strains have begun to acquire resistance to vancomycin, the drug of last resort (27,59,61). Two new compound classes have been introduced to treat S. aureus infections since 2000, and the emergence of resistance to those is now a concern (40,61). Thus, novel compounds and strategies to overcome multiply resistant S. aureus infections are needed.…”
mentioning
confidence: 99%
“…Many S. aureus strains are resistant to all betalactams, the most effective class of antibiotics in history (20,59). Some of these methicillin-resistant S. aureus (MRSA) strains have begun to acquire resistance to vancomycin, the drug of last resort (27,59,61). Two new compound classes have been introduced to treat S. aureus infections since 2000, and the emergence of resistance to those is now a concern (40,61).…”
mentioning
confidence: 99%
“…Both laboratory (RN4220) and clinical (Newman) strains of DtarO mutants were attenuated in their ability to attach to HCECs compared with the parental strains, and this was independent of growth phase. 25 Confocal microscopy also showed that laboratory strain (RN6390) tarO-null mutants could not attach to HCECs (Fig. 3).…”
Section: A New Target For Staphylococcus Aureus Keratitismentioning
confidence: 94%
“…Targocil showed excellent activity against S. aureus isolates from suspected cases of bacterial keratitis, including both methicillin-sensitive Staphylococcus aureus and MRSA, with MICs of 1-2 mg/mL (Table 2). 25 This compound inhibits the growth of a number of S. aureus isolates, including MRSA strains. Furthermore, a standard broth microplate checkerboard synergy assay was conducted to determine the extent to which targocil and antibiotics of other classes, including vancomycin, ciprofloxacin, methicillin, and gentamicin, interact with S. aureus strains.…”
Section: A New Target For Staphylococcus Aureus Keratitismentioning
confidence: 99%